Spanglerodessus shorti and Incomptodessus camachoi, new genera and species of Bidessini from Guyana and Venezuela (Coleoptera: Dytiscidae: Hydroporinae) - Miller, Kelly B.; Garcia, Mauricio (Zootaxa, 2011)
Two new genera and species are described. Spanglerodessus n. gen. is described to include the single new species, S. shorti n. sp. from localities in eastern Venezuela and western Guyana. This genus is similar to Bidessodes Régimbart and Fontidessus Miller and Spangler, but differs from the first in having overall dark coloration, lack of dorsal color patterns or iridescence, a broad lateral bead, and broad and robust habitus. From Fontidessus the genus differs in being much more robust and lacking natatory setae. Incomptodessus n. gen. is described to include a single new species I. camachoi n. sp. from localities in the upper Orinoco River basin in Amazonas and Bolivar States. This genus differs from similar bidessine genera, Sharphydrus Omer-Cooper, Tyndallhydrus Sharp, Liodessus Guignot and Neobidessus Young, in having impunctate metacoxae and metaventrite and lacking basal striae on the elytra.